The spatial and non-spatial properties of single-units in the anterior retrosplenial cortex of the freely-moving rat - Wynne, Paul (Trinity College (Dublin, Ireland). School of Psychology, 2016)
The purpose of this study was to describe the spatial and non-spatial properties of single-units in the anterior retrosplenial cortex (RSC) of the freely moving rat. A total of five male Lister Hooded rats were implanted with bundles of four or eight tetrodes aimed at the anterior RSC. Each tetrode was made of a bundle of four microwires which were mounted onto a small driveable microdrive. Rats were connected to the recording system which allowed for animal position tracking via two mounted infrared LEDs. Rats were then placed onto a raised circular platform, with 0.3cm high perimeter walls, screened for the presence of single-units while performing a pellet chasing task for 16 minutes. Units recorded were quickly analysed for any spatial or head direction firing preference as well as theta-modulation. Units which displayed either location or head direction dependent firing then underwent recording sessions where the environment was changed, see Table 1. Units which displayed no location or head direction dependent firing were not subject to these recording sessions. Units which were theta-modulated or theta-skipping were also not subject to the recordings sessions. However, the screening session for these units were saved for further analysis.
Keywords: Psychology, Ph.D.; PhD Trinity College Dublin, 2016